Surface Covering Protective VegetableNursery for Hot Arid Climate - Ram, Hanuman; Samadia, D K; Verma, A K; Gurjar, P S (Indian Horticulture, 2024)
The north-western part of India is distinct for the promotion of arid horticulture owing to vast land resources and scope for cultivation of daily-need vegetable crop plants. Tomato, chilli and brinjal are high in consumption and abundant in demand. The unavailability of quality and disease-free seedlings during the transplanting period is a big problem and results in poor harvest. Extreme high and low-temperature condition is the prime constraint for the raising of seedlings in time with common practices of nursery. In this context, ICAR-CIAH, Bikaner has developed SOP’s as a package of practices and defined as technology “Surface covering protective vegetable nursery scheme” for seedling production year-round. It is a local fabrication, simple, cost-efficient and an excellent mechanism to escape from the severity of temperature. Coat-type frames are arranged on raised beds (50-60 sq. m plot area and a pair bed of 25 × 01 m) and transparent polythene (120-200 gauge) and 40 mesh insect-proof nylon-net sheet is used to cover the structures in respect of winter and summer season sowing under hot arid climate.